Mocking the age : the later novels of Philip Roth - Safer, Elaine B. (SUNY series in modern Jewish literature and culture., 2006)
The first comprehensive assessment of Philip Roth's later novels, Mocking the Age offers rich and insightful readings that explore how these extraordinary works satirize our contemporary culture. From The Ghost Writer to The Plot Against America, Roth uses humor to address deadly serious matters, including social and political issues, psychological problems, postmodern concerns, and the absurd. In her clear and extensive analyses of these works, Elaine B. Safer looks at how Roth's approach to the comic incorporates the self-deprecating humor of Jewish comedians, as well as the humor of nineteenth-century Eastern European Jewish storytellers and such twentieth-century writers as Bernard Malamud and Saul Bellow. Filling the void on critical examinations of Roth's later work, Safer's book provides a thorough appraisal of Roth's lifetime accomplishment and an essential evaluation of his comic genius. Book jacket.